1986
DOI: 10.1016/0736-5748(86)90066-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of opiates on the growth of neuron‐enriched cultures from chick embryonic brain

Abstract: Neuron-enriched cultures derived from 6-day-old chick embryo cerebral hemispheres were treated with morphine or methadone, 10(-5) M or 10(-6) M, on days 4-6 or 6-8 in culture and were evaluated morphologically and biochemically at day 9 using phase contrast microscopy and choline acetyltransferase activity (ChAT) as a cholinergic marker. The treatment of the cultures with morphine markedly affected their growth pattern; specifically, we observed an increased number of flat cells presumptively glia, and aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…During development, endogenous opioid neuropeptides typically act by inhibiting the growth of the nervous system (21,77,78). Opiate drugs such as morphine also affect neural development (9,12,14,16,17,42,52,54,58,62,66,70,74). Presumably opiate drugs disrupt the normal interactions between endogenous opioid peptides and their receptors.…”
Section: Introductionmentioning
confidence: 99%
“…During development, endogenous opioid neuropeptides typically act by inhibiting the growth of the nervous system (21,77,78). Opiate drugs such as morphine also affect neural development (9,12,14,16,17,42,52,54,58,62,66,70,74). Presumably opiate drugs disrupt the normal interactions between endogenous opioid peptides and their receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that endogenous opioid peptides, products of proenkephalin or pro-opiomelanocortin, inhibit DNA synthesis in in vitro neuronal or glial cultures or in neuroblastoma cells (1)(2)(3)(4). These studies were supported by the observation that opioid antagonists could stimulate DNA synthesis and proliferation in some neuroblastoma cell lines.…”
mentioning
confidence: 96%
“…Now that opioid receptors have been cloned, they can be stably overexpressed in differentiated cell lines with properties characteristic of neurons (Yasuda et al, 1993;Banerjee et al, 1996: Toth et al, 1995, and the molecular basis of receptor desensitization can be directly addressed. Opioid peptides are abundant during embryonic development (Sakellaridis et al, 1986), Opiates and opioid peptides, acting through the K-, p-, and ô-opioid receptors, have been shown to dissociate initially Gã,dy trimeric complexes, thereby inhibiting adenylate cyclase and blocking calcium entry either by hyperpolarizing K~channels (Grunt and Williams, 1993) or directly blocking activation of N-type calcium channels (Herlitze et al, 1996;Ikeda, 1996). Desensitization and tolerance following prolonged exposure to agonists are commonly observed with morphine and other opioids used in the treatment of pain.…”
mentioning
confidence: 99%